2013
DOI: 10.4269/ajtmh.13-0033
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Introducing RDTs for Malaria Diagnosis as Compared to Microscopy and Presumptive Diagnosis in Central and Peripheral Public Health Facilities in Ghana

Abstract: Cost-effectiveness information on where malaria rapid diagnostic tests (RDTs) should be introduced is limited. We developed incremental cost-effectiveness analyses with data from rural health facilities in Ghana with and without microscopy. In the latter, where diagnosis had been presumptive, the introduction of RDTs increased the proportion of patients who were correctly treated in relation to treatment with antimalarials, from 42% to 65% at an incremental societal cost of Ghana cedis (GHS)12.2 (US$8.3) per a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 55 publications
(71 reference statements)
4
46
0
Order By: Relevance
“…Similar ICERs have been reported elsewhere [7,10,11,13,29]. For instance, the incremental cost per patient correctly treated by replacing microscopy with RDTs in public health facilities was $3.6 in Ghana (2009 prices) [13], $1.78 in low malaria transmission areas in Uganda, and $8.9 in high malaria transmission areas in Uganda (2011 prices) [11]. Differences in study design should be noted, however, when comparing results, and our study was distinctive for several reasons.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar ICERs have been reported elsewhere [7,10,11,13,29]. For instance, the incremental cost per patient correctly treated by replacing microscopy with RDTs in public health facilities was $3.6 in Ghana (2009 prices) [13], $1.78 in low malaria transmission areas in Uganda, and $8.9 in high malaria transmission areas in Uganda (2011 prices) [11]. Differences in study design should be noted, however, when comparing results, and our study was distinctive for several reasons.…”
Section: Discussionsupporting
confidence: 83%
“…Results were also sensitive to the prevalence of malaria in febrile patients, specificity and sensitivity of the test, cost of testing and medicines, whether nonmalaria febrile illness was a bacterial or selfresolving viral infection, the efficacy of antimalarials and antibiotics taken, and whether patients take medicines as advised [9]. The literature shows that RDTs tend to be more cost-effective than microscopy when compared with a presumptive diagnosis [7,11,12], while the cost-effectiveness of RDTs compared with microscopy depends on the relative cost of the tests, as well as their specificity and sensitivity in routine use [10,[13][14][15].…”
Section: Introductionmentioning
confidence: 98%
“…Analyses of the incremental economic cost per fever case managed have been published for four studies included in this synthesis. Where mRDTs were compared with microscopy (Afgh1, Ghan1, and Cam1), mRDTs were cost saving or costs were similar in Afghanistan, 59 with an incremental provider cost per fever case managed ranging from 0.20 to 1.11 USD in in Ghana 60 and Cameroon 61 (2011 USD). Where mRDTs were compared with clinical diagnosis, the incremental provider cost per fever case managed ranged from 0.24 to 10.9 USD across different transmission levels and provider types in Afghanistan, Ghana, and Uganda (2011 USD).…”
Section: Discussionmentioning
confidence: 99%
“…mRDT has been shown to be effective even in low transmission areas [25]. Some studies in Africa revealed that using mRDT enhanced correct treatment of malaria more than microscopy [26] [27]. It is important that these wrong perceptions among doctors about mRDT be addressed so that doctors effectively play leading roles aimed at using mRDT as an important tool for implementing the WHO malaria Test, Treat and Trackinitiative.…”
Section: Discussionmentioning
confidence: 99%